2014
DOI: 10.1177/0961203314563135
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical right ventricle systolic dysfunction in childhood-onset systemic lupus erythematosus: insights from two-dimensional speckle-tracking echocardiography

Abstract: The present study, using a new and more sensitive technique, revealed subclinical RV systolic dysfunction in c-SLE patients that may have future prognostic implications. The novel association of asymptomatic RV dysfunction with neuropsychiatric manifestations and antiphospholipid antibodies may suggest common physiopathological pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
4
24
1
1
Order By: Relevance
“…LV peak longitudinal systolic strain correlated negatively with SLE disease activity index and cumulative exposure to traditional and diseaserelated CV risk factors [48]. Abnormalities in RV strain have also been reported [11].…”
Section: Systolic Functionmentioning
confidence: 95%
“…LV peak longitudinal systolic strain correlated negatively with SLE disease activity index and cumulative exposure to traditional and diseaserelated CV risk factors [48]. Abnormalities in RV strain have also been reported [11].…”
Section: Systolic Functionmentioning
confidence: 95%
“…The current study confirmed these data for positive aCL antibod- The current study revealed that right ventricular function was more impaired than left ventricular function, similar to findings by Tektonidou et al (19) who declared that all parameters of RV diastolic function showed more pronounced impairment than the respective LV parameters. This dissociation may reflect a preferential involvement or a higher susceptibility of the right ventricle, which can emphasize the role of microvascular disease in the RV more than in the LV, due to its smaller mass than the LV (27); pulmonary hypertension may also have a role (20,27). In that context, pulmonary hypertension and primary APS were the strongest independent predictors of a prolonged duration time.…”
mentioning
confidence: 87%
“…Pulmonary artery hypertension is a rare but severe complication of SLE . The mechanism of PAH in SLE is dormant, but it progresses rapidly in that many patients are clinically silent: that is, without manifestations of SLE activity . According to literature reports, the incidence of PAH in patients with SLE has gradually increased in recent years, and it would increase with lengthening of the disease duration.…”
Section: Discussionmentioning
confidence: 99%